Sintesis Tembaga (II) Sulfat Pentahidrat (CuSO₄.5H₂O) Dari Limbah Kabel Tembaga (Cu) Dengan Proses Kristalisasi Dingin - Febby Vania; Pujangga Tirta Kusuma; Ni Ketut Sari (Jurnal Inovasi Teknik Kimia, 2026)
Copper cable waste is a type of electronic waste with high copper content and potential for reuse as a raw material for value-added products. This study synthesized copper(II) sulfate pentahydrate (CuSO₄·5H₂O) from copper cable waste through cold crystallization and determined the optimum process conditions. Copper was dissolved in 65% nitric acid (HNO₃) to form Cu²⁺ ions, followed by the addition of sulfuric acid (H₂SO₄) at concentrations of 16–24% and heating until saturation. Crystallization was conducted at 8–24°C for 48 h. The crystals were separated, dried, and analyzed using XRF, XRD, and hydration analysis. The highest yield, 89.43%, was obtained at 22% H₂SO₄ and 8°C. XRD confirmed the dominant triclinic CuSO₄·5H₂O phase, while hydration analysis showed a CuSO₄:H₂O molar ratio of 1:5. Response Surface Methodology with CCD showed strong model fitness, with R² values of 0.997 for yield and 0.9959 for Cu content.